Dynamics of Human Aggression : Theoretical Foundations, Clinical Appliations. - Rizzuto, Ana-Maria (Brunner-Routledge, 2003)
Aggression is often thought of as involving hostility, anger, or destructiveness. The authors of book challenge this view, and justify their new theory to readers on both the theoretical and clinical fronts.